Blood pressure indices and cardiovascular disease mortality in persons with or without diabetes mellitus. Issue 1 (January 2018) - Gomadam, Pallavi; Shah, Amit; Qureshi, Waqas; Yeboah, Phyllis N.; Freedman, Barry I.; Bowden, Donald; Soliman, Elsayed Z.; Yeboah, Joseph
Abstract : Background: We examined the associations between blood pressure indices (SBP, DBP, mean arterial pressure and pulse pressure) and cardiovascular disease (CVD) mortality among persons with or without diabetes mellitus (NON-DM) in a multiethnic cohort. Methods: We included 17 650 participants from National Health and Nutrition Examination Survey III and 1439 participants from Diabetes Heart Study (total n  = 19 089, 16.3% had diabetes mellitus, mean age 48.5 years, 44.4% white, 27.1% black, 28.5% other race, 54.4% women). Cox proportional hazard, cubic spline and area under the curve analyses were used to assess the associations. CVD death was ascertained via social security registry or the National Death Index. Results: After a mean (SD) of 16.2 (6.1) years of follow-up, 17.9% of diabetes mellitus and 8.8% of those NON-DM died of CVD. Diabetes mellitus was associated with an increased risk of CVD death [hazard ratio (95% confidence interval): 1.50 (1.25–1.82)]. One SD increase in SBP was significantly associated with CVD mortality in NON-DM [1.28 (1.18–1.39)] but not diabetes mellitus [1.04 (0.88–1.23)] in the full Cox models. Adjusted cubic spline analysis showed significant nonlinear but different association between SBP and CVD mortality among diabetes mellitus (U-shaped) and NON-DM (J-shaped). The C -statistics of our full model in NON-DM and diabetes mellitus were (0.888 vs. 0.735, P  < 0.001). SBP showed a trend toward improving C statistics in NON-DM but not diabetes mellitus. Conclusion: The association between SBP and CVD mortality risk is nonlinear but different in diabetes mellitus (U-shaped) and NON-DM (J-shaped), explaining why aggressive blood pressure lowering may have different outcomes in these two groups. Abstract : Supplemental Digital Content is available in the text